Preoperative and postoperative features of non-functioning pituitary adenomas: a single center experience - Şişman, Pınar; Özbiçer, Buket; Öz Gül, Özen; Cander, Soner; Soyak, Halime; Ersoy, Canan (The European Research Journal, 2019)
Objectives: The main purposes of surgical treatment for non-functioning pituitary adenomas are removal of the pressure on the surrounding structures, especially the hypophyseal gland and visual tissue, and the normalization of hypophyseal functions. In our study, we retrospectively reviewed postsurgical follow-up of patients with non-functioning pituitary adenoma treated at our institution in a period of 15 years of monitoring and evaluated surgical success, complication rate and recurrence rates in accordance with the literature. Methods: This study included 55 patients who had undergone surgery between 2000 and 2014 and who were followed-up postoperatively at our center. Preoperative and postoperative anterior pituitary hormones, complete resection and recurrence and also postoperative recovery of endocrinological and ophthalmological functions were statistically evaluated using file data of the patients. Results: There were 33 (60%) males and 22 (40%) females. It was observed that the adenoma caused pressure on the optic chiasm in 11 patients and infiltrated cavernous sinus in 9 patients. Postoperative mean follow-up was 75.14 ± 43.01 months. Seventeen (30.9%) patients had recurrence after complete resection. Postoperative persistence and deterioration rates were 12.2% and 26.6% in adrenal insufficiency, 12.2% and 26.6% in central hypothyroidism, respectively, while 12.2% worsening in central hypogonadism. Ophthalmologic findings were resolved in 62.5% of patients and persisted in 37.5% of the patients. Conclusions: The adenoma size and experience of the surgeon in non-functioning pituitary adenomas are the most important factors affecting surgical success. We recommend that operations should be performed in experienced centers, preoperative and postoperative endocrinological evaluations and long-term follow-up should be done.